Dielectric susceptibility behaviour in the incommensurate phase of TlInS2 - Mikailov, FA; Basaran, E; Mammadov, TG; Seyidov, MY; Sentürk, E (Elsevier Science Bv, 2003)
Peculiarities of the temperature behaviour of the dielectric susceptibility of TlInS2 in the temperature interval of incommensurate (IC) phase have been theoretically investigated on the basis of recently suggested two-sublattice model of the phase transitions in TlInS2, which is based on the hypothesis about the coexistence of improper and proper ferroelectricity and also the presence of type I and type II incommensurations in the same compound. The temperature dependence of the dielectric constant of TlInS2 in the IC phase was calculated. An agreement between theoretical and experimental results has been obtained. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: ferroelectrics; dielectric response; phase transitions